Environmental Efficiency of Node Cities in Chinese Section of Silk Road Economic Zone and Its Influencing Factors - Lei Zhang; Xinyu Peng (Discrete Dynamics in Nature and Society)
This paper adopts an environmental data envelopment analysis (DEA) model containing pollution emissions to measure the environmental efficiency of node cities in the Chinese section of Silk Road Economic Zone (SREZ) in 2011–2020 and verifies the convergence of the environmental efficiency. The results show that the ten node cities had an overall low environmental efficiency and a large gap in environmental efficiency, highlighting the necessity of cross-regional cooperation in emission reduction and the promotion of environmental technologies between regions; the environmental efficiency gaps between node cities and between the three regions started to narrow in 2016 and 2018, respectively, showing a certain convergence trend. In addition, the Tobit model was called to analyze the factors affecting environmental efficiency, revealing that per-capita gross domestic product (GDP), foreign trade, and population density promote environmental efficiency, while the proportion of the secondary industry, number of authorized patents, and regional feature significantly suppresses environmental efficiency. Finally, several suggestions were provided to reduce regional pollution emissions and increase China’s environmental efficiency, according to the results of empirical analysis.